2012
DOI: 10.1097/ede.0b013e31826b7f97
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High Ambient Temperature on Emergency Room Visits

Abstract: Increased temperatures were found to have same-day effects on ER admission for several outcomes. Age and race/ethnicity seemed to modify some of these impacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
152
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(178 citation statements)
references
References 34 publications
24
152
0
2
Order By: Relevance
“…Each 10 8 F increase in outdoor heat was found to increase respiratory hospitalization rates 12.3% in Mediterranean cities (14), 16.1% in New York, NY (12), and 19.3% in a metaanalysis of worldwide heat-morbidity studies (6). This difference cannot be explained by differences in exposure metrics, because our estimates changed little with alternate exposure metrics.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…Each 10 8 F increase in outdoor heat was found to increase respiratory hospitalization rates 12.3% in Mediterranean cities (14), 16.1% in New York, NY (12), and 19.3% in a metaanalysis of worldwide heat-morbidity studies (6). This difference cannot be explained by differences in exposure metrics, because our estimates changed little with alternate exposure metrics.…”
Section: Discussionmentioning
confidence: 41%
“…U.S. studies of heat and respiratory morbidity have been limited to single cities (12, 15) or single states (California [10,11,16], New York [13]) or were retrospective studies of single heat waves (17-19). Worldwide, large heterogeneity exists between temperature-morbidity studies from different locations (6, 20).…”
mentioning
confidence: 99%
“…Similar findings on low temperature and higher stroke occurrence were also reported in South Korea, 23 northern Portugal, 24 and Hong Kong. 8 On the other hand, hot temperature was linked to higher stroke risk in studies in Scotland, 25 Mantua (Italy), 9 New York City, 26 California, 27 Brisbane (Australia), 28 and 4 cities in Korea. 29 In the present study, we found that the associations between temperature and stroke mortality were often nonlinear-both low and high temperatures were linked to more stroke deaths.…”
Section: Figurementioning
confidence: 99%
“…Во время волн жа-ры, по данным различных исследователей, в Европе, Азии, США, Австралии отмечено увеличение количества вызовов скорой ме-дицинской помощи (СМП) [38][39][40], экстренных госпитализа-ций в отделения неотложной помощи [41][42][43], общего числа го-спитализаций [44][45][46][47], амбулаторных обращений к врачу [48,49]. В ряде исследований ССЗ входят в число основных причин ухуд-шения состояния.…”
Section: терапевтический архив 9 2015unclassified
“…), повышение среднесуточной температуры воздуха на 10 °F (12,2 °С) ассоциировалось с ростом числа экстренных госпита-лизаций в тот же день по поводу ИБС на 1,7%, ишемического ин-сульта на 2,8%, нарушений ритма сердцана 2,8%, гипотонии на 12,7%, сахарного диабета на 4,3%, кишечных инфекций на 6,1%, дегидратации на 25,6%, острой почечной недостаточности на 15,9%; число госпитализаций в связи с перегреванием организма увеличилось почти в 4 раза. Число гипертонических кризов и ге-моррагических инсультов во время волн жары в Калифорнии уменьшилось [43].…”
Section: терапевтический архив 9 2015unclassified